Quantitative In Situ Analysis of the Anterior Cruciate Ligament: Length, Midsubstance Cross-sectional Area, and Insertion Site Areas. (January 2016) - Fujimaki, Yoshimasa; Thorhauer, Eric; Sasaki, Yusuke; Smolinski, Patrick; Tashman, Scott; Fu, Freddie H.
Background: Quantification of the cross-sectional area (CSA) of the anterior cruciate ligament (ACL) in different loading conditions is important for understanding the native anatomy and thus achieving anatomic reconstruction. The ACL insertion sites are larger than the ACL midsubstance, and the isthmus (region of the smallest CSA) location may vary with the load or flexion angle. Purpose: To (1) quantify the CSA along the entire ACL, (2) describe the location of the ACL isthmus, (3) explore the relationship between ACL length and CSA, and (4) validate magnetic resonance imaging (MRI) for assessing the CSA of the midsubstance ACL. Study Design: Descriptive laboratory study. Methods: Eight cadaveric knees were dissected to expose the ACL and its attachments. Knees were positioned using a robotic loading system through a range of flexion angles in 3 loading states: (1) unloaded, (2) anterior tibial translation, and (3) combined rotational load of valgus and internal torque. Laser scanning quantified the shape of the ACL and its insertion site boundaries. The CSA of the ACL was measured, and the location of the isthmus was determined; the CSA of the ACL was also estimated from MRI and compared with the laser-scanned data. Results: The CSA of the ACL varied along the ligament, and the isthmus existed at an average (±SD) of 53.8% ± 5.5% of the distance from the tibial insertion center to the femoral insertion center. The average CSA at the isthmus was smallest in extension (39.9 ± 13.7 mm 2 ) and increased with flexion (43.9 ± 12.1 mm 2 at 90°). The ACL length was shortest at 90° of flexion and increased by 18.8% ± 10.1% in unloaded extension. Application of an anterior load increased the ACL length by 5.0% ± 3.3% in extension, and application of a combined rotational load increased its length by 4.1% ± 3.0% in extension. Conclusion: The ACL isthmus is located almost half of the distance between the insertion sites. The CSA of the ACL at the isthmus is largest with the knee unloaded and at 90° of flexion, and the area decreases with extension and applied loads. The CSA at the isthmus represents less than half the area of the insertion sites. Clinical Relevance: These results may aid surgical planning, specifically for choosing a graft size and fixation angle that most closely matches the native anatomy and function across the entire range of knee motion.